2023
DOI: 10.1002/ctm2.1331
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoural microbiome can predict the prognosis of hepatocellular carcinoma after surgery

Abstract: Background The dismal prognosis of hepatocellular carcinoma (HCC) is closely associated with characteristics of the tumour microenvironment (TME). Recent studies have confirmed the presence and potential influence of the microbiome in TME on cancer progression. Elucidating the relationship between microbes in the TME and cancer could provide valuable insights into novel diagnostic markers and therapeutic strategies for HCC and thus warrants a closer investigation of the role of intratumoural microbiome in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This raises the intriguing possibility of employing microbial DNA detection as a non-invasive prognostic marker for CRC, offering clinical benefits such as early intervention and treatment stratification. The potential use of microbial markers as prognostic indicators in patients with CRC is in accordance with the broader concept of microbial signatures for predicting patient outcomes [41][42][43][44][45]. Identifying highrisk patients who could benefit from more aggressive treatment is a common objective.…”
Section: Discussionmentioning
confidence: 82%
“…This raises the intriguing possibility of employing microbial DNA detection as a non-invasive prognostic marker for CRC, offering clinical benefits such as early intervention and treatment stratification. The potential use of microbial markers as prognostic indicators in patients with CRC is in accordance with the broader concept of microbial signatures for predicting patient outcomes [41][42][43][44][45]. Identifying highrisk patients who could benefit from more aggressive treatment is a common objective.…”
Section: Discussionmentioning
confidence: 82%
“…The inclusion criteria for patients with ascites secondary to HCC were as follows ( 40 , 41 ): (i) patients were pathologically diagnosed with HCC and were confirmed by examination by one or more pathologists; (ii) patients were diagnosed with peritoneal fluid and underwent abdominal paracentesis; (iii) tumor cells were found in the peritoneal fluid by cytological examination; (iv) patients’ clinical data are available in the Electronic Medical System. The exclusion criteria for patients with ascites secondary to HCC were as follows: (i) patients with benign ascites, such as renal insufficiency, and hypoproteinemia; (ii) patients with pleural effusion; (iii) patients with a history of other cancers within the past 5 years; (iv) patients with false-malignant ascites after a combined course of chemotherapy; (v) patients with incomplete clinical information.…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al identified two hepatotypes based on the microbial profile clustering, representing independent prognostic factors in patients with resected HCC. 267 Song et al developed a microbiome-related score model based on 27 microorganisms that acted as an independent prognostic factor for HCC patients. 268 …”
Section: Prognostic Role Of Intratumoural Microbiotamentioning
confidence: 99%